(untitled) (Annals of Medical Research, 2021)
Aim: In this retrospective study, it was aimed to evaluate the clinical and pathological features of cases diagnosed with OKC and the recurrence status after treatment options.Material and Methods: 41 patients who were treated with the diagnosis of OKC between December 2015-June 2018 and whose pre- and post-treatment follow-up data could be reached were included in the study. As the variables examined, age and gender of the patients, localization of cyst and radiographic features, histopathological findings, treatment methods and recurrence status were investigated retrospectively.Results: Of 41 patients with a mean age of 36.68±17.89 (age range 13 to 78) years, 24 (58.5%) were males and 17 (41.5%) were females. It was determined that OKCs were observed most frequently in the third decades (21.9%) followed by the second and fourth decades (19.5%). The incidence of OKC was determined to be higher in the mandible (80.5%) than in the maxilla (19.5%). The recurrence was observed in 7 of 41 cases (17.1%) after the treatment. The recurrence was detected particularly in mandibular posterior and larger lesions. The fact that five of the seven recurrent cases were parakeratotic and likewise five cases were treated with enucleation was noteworthy.Conclusions: The treatment and prognosis of OKC should be determined according to the condition of the case and the treatment protocol should be managed accordingly.Keywords: Odontogenic cyst; odontogenic keratocyst; decompression; retrospective; recurrence.